Interfacing theology, culture and the English language - Dousel, Edmalyn Grace Gaston (2008)
Texts among foreign language textbooks usually had little or no reference to the spiritual dimension of life. This study focused on interfacing theological concepts and the English language through 15 English language lessons specifically designed for Asian theological seminaries. There were 5 stages of data gathering. A learning/teaching manual, English for Theological Studies: English Made Easy for Seminaries, was written. Compatibility of the language lessons to the context and culture in the seminary was established. It was found that difficulty in comprehending theological concepts was due to the students' skills in the English language and their religious and cultural backgrounds. The effectiveness of the manual was observed in the improvement of oral and written output of the students. It was establshed that English for Theology is classifiable as English for Specific Purposes.